Chrysophanol Ameliorates Hemin-Induced Oxidative Stress and Endoplasmic Reticulum Stress by Regulating MicroRNA-320-5p/Wnt3a Pathway in HT22 Cells. (29th July 2022) - Zhao, Xu; Qiao, Dongge; Guan, Dongsheng; Wang, Kun; Cui, Yinglin
Abstract : Oxidative stress, endoplasmic reticulum (ER) stress, and neuronal cell apoptosis have been considered as the main pathogenesis factors of brain injury after intracerebral hemorrhage (ICH). Chrysophanol (CHR) has been proved to have neuroprotective effects, but the role and underlying mechanisms of CHR in ICH remain unclear. HT22 cells were dealt with hemin to mimic an in vitro ICH model and then subjected to treatment with or without CHR. The cell viability, apoptosis, ER stress, and oxidative stress were evaluated by conducting the cell counting kit-8 (CCK-8), TdT-mediated dUTP nick end labeling (TUNEL) staining assays, western blot, and corresponding kit, respectively. Further, microRNA-sequencing, bioinformatic analysis, dual-luciferase reporter method, and rescue experiments were conducted to explore the molecular mechanisms of CHR alleviating hemin-induced ER in HT22 cell. Our data revealed that CHR increased cells viability, antiapoptosis, anti-ER stress, and antioxidative stress under conditions of hemin-induced HT22 cell injury. Mechanically, it was observed that Wnt3a was competitively sponged by miR-320-5p, and CHR activated β -catenin pathway by regulating miR-320-5p/Wnt3a molecular axis. Finally, results from the rescue experiment suggested that CHR inhibited hemin-induced cells apoptosis, ER stress, and oxidative stress through regulating the miR-320-5p/Wnt3a axis in HT22 cells. In conclusion, CHR prevented hemin-induced apoptosis, ER stress, and oxidative stress via inhibiting the miR-320-5p/Wnt3a/ β -catenin pathway in HT22 cells. Our results certified that CHR could be served as a promising treatment for brain damage following ICH.